The use of interval-training methods by coaches of well-trained middle- to long-distance runners - Arran Parmar; Thomas Jones; Philip Hayes (International Universities Strength and Conditioning Association, 2021)
Limited research exists on how coaches of well-trained middle- to long-distance runners implement interval-training (IT) methods. IT interventions within research focus on physiological measures whereas coaches focus on performance, leading to a disconnect between the IT methods utilized in research and practice. This study aimed to identify how coaches of well-trained middle- to long-distance runners implement IT methods within the training regimen. A survey was developed that comprised 5 sections: participant demographics, the use of IT, the type and characteristics of IT, recovery from IT, and reasons for including IT. Thirty (29 male, 1 female) coaches completed the survey. All coaches prescribed short, medium and long work intervals into the training regimen using race paces of 800m, 3000m, and 10000m, respectively, to prescribe intensity. Active recovery modalities were prescribed by the majority of coaches between sets and repetitions of all types of work intervals. The majority of coaches periodized the type of work interval prescribed relative to the competition date, with 1-2 IT sessions prescribed per week, year-round. Most coaches reported learning about IT primarily from their own training and coaching books, however, the most valuable sources of education for IT were ranked as scientific literature, coaching courses and workshops.